PEMANFAATAN LIMBAH SAMPAH PLASTIK DENGAN METODE ECOBRICK DI PEKON GUNUNG KEMALA - Fitriani, Agus Sutrisno; Fadillah, Mahasiswa KKN Univeristas Lampung (BUGUH: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
Ecobrick is a way of handling plastic waste by packing clean and dry plastic into plastic bottles to the specified density. The work program Utilizing Plastic Waste Using the Ecobrick Method is aimed at reducing plastic waste in the village and making the people of Gunung Kemala Village more skilled at processing waste as a new, high-value business opportunity. This article attempts to provide an overview and explanation regarding the work program for making ecobrick, including the process, stages, results, and benefits. As a result of this activity, the community received new understanding and insight in terms of utilizing household plastic waste. This article is limited to the implementation of the Gunung Kemala Village KKN Period 1 2023.